2009
DOI: 10.1007/s10311-009-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of zinc ions from aqueous solution by the microalga Scenedesmus obliquus

Abstract: Aquatic environments are often exposed to toxic heavy metals, which gain access to the food chain via microalgae and may cause severe problems at higher trophic levels. However, such a metabolic specificity can be taken advantage of in bioremediation strategies. The potential of a novel wild strain of Scenedesmus obliquus, previously isolated from a heavy metal-contaminated site in northern Portugal, to remove Zn from aqueous solutions was thus studied, using several initial concentrations. The removal extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…The results showed that lead(II) adsorption could covalently bond with C-, N-, O-and P-containing functional groups. As previously reported, the functional groups (carboxylate, hydroxyl, amino and phosphate) on bacterial cell surface were responsible for lead(II) adsorption (Monteiro et al 2011;Sedighi et al 2012). Thus, it was rational to speculate that adsorption of lead(II) by strain BAPb.1 mostly occurred on the cell surface.…”
Section: Sem-edx Analysismentioning
confidence: 57%
“…The results showed that lead(II) adsorption could covalently bond with C-, N-, O-and P-containing functional groups. As previously reported, the functional groups (carboxylate, hydroxyl, amino and phosphate) on bacterial cell surface were responsible for lead(II) adsorption (Monteiro et al 2011;Sedighi et al 2012). Thus, it was rational to speculate that adsorption of lead(II) by strain BAPb.1 mostly occurred on the cell surface.…”
Section: Sem-edx Analysismentioning
confidence: 57%
“…The advantages of biosorption, which is based on ionic interactions and complex formations between metal ions and the functional groups of the biosorbent, are low operating cost, selectivities for specific metals, relatively high efficiencies, and minimisation of the volumes of chemical and biological sludge (Flouty and Estephane 2012;Mane and Bhosle 2011). Several live micro-organisms (algae, bacteria, fungi and yeast) have been investigated for metal adsorption from polluted waters, and algae especially have proven to be very useful for this purpose because of their availability, low costs and ability to uptake large quantities of heavy metals (Monteiro et al 2011). Compared to fungi and yeast, algae have been proved to have higher heavy metal biosorption capacities because of their cell walls, which are composed of a fibre-like structure and an amorphous embedding matrix of various polysaccharides (Akhtar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Natural processes like surface runoffs, weathering and/or erosion and anthropogenic activities like mining, industrial effluents, agricultural runoffs and sewage have led to the accumulation of toxic metals and their derivatives like nanoparticles in the environment (Paula et al 2013;Zhao et al 2012). Zinc and zinc oxide nanoparticles (ZnO NPs) are of high concern because of their increasing demand in electroplating, galvanization, cosmetics, sunscreens, paints, food industry, anticancer drugs, antimicrobials, ceramics, and semiconductors (Monteiro et al 2011;Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%